IMPROVING TEACHER PERFORMANCE IN SCHOOLS THROUGH HUMANISTIC LEADERSHIP - Fauzan Fauzan; Fajriyah Fajriyah; Moh Dannur; Wawan Ridwan (LP2M IAI Al Khairat Pamekasan, 2023)
The leadership model in an educational setting influences the effectiveness of the learning process in schools. Effective principal leadership can improve teacher performance and the quality of education. Humanistic leadership can be applied at all levels of education, including early childhood education (PAUD). The education process starts at the lowest education level, namely PAUD. This level of education needs full attention because it is the foundation of children's education, where early childhood is at the best stage of physical and brain development. The creation of quality PAUD is influenced by the leadership of the school principal. With humanistic leadership, it is hoped that the principal is able to meet the basic needs of teachers, which can create teacher satisfaction so that they can improve their performance. Job satisfaction and teacher performance have a very close relationship because it is important and is an aspect of organizational psychology.